Vitamin D role in prevention of cancer: Overview - T G Shrihari (Indian Journal of Medical and Paediatric Oncology)
Vitamin D is the name given to a group of fat-soluble prohormones. Two major forms of Vitamin D that are important to humans are Vitamin D2 or ergocalciferol and Vitamin D3 or cholecalciferol. Vitamin D2 is made naturally by the body when the skin is exposed to ultraviolet radiation (in particular, ultraviolet B [UVB] radiation) in sunlight. Vitamin D2 and Vitamin D3 can also be commercially manufactured. The active form of Vitamin D in the body is 1,25-dihydroxyvitamin D or calcitriol, which can be made from either Vitamin D2 or Vitamin D3. Evidence suggests that Vitamin D helps in the prevention of various cancers such as breast cancer, colorectal cancer, prostate cancer, head and neck cancer, and other cancers. This review article briefs about the role of Vitamin D in the prevention of cancer.